Cataract Surgical Uptake Among Older Adults in Ghana - Ackuaku-Dogbe, EM (Ghana Med J, 2015)
OBJECTIVES: In sub-Saharan Africa, cataract surgical services are highly inadequate and surgical uptake for cataract is low. This paper describes cataract surgical uptake among older adults in Ghana. METHODS: This work was based on World Health Organization's multi-country Study on global Ageing and adult health (SAGE), conducted in six countries including Ghana. Wave one of SAGE in Ghana was conducted in 2007–2008 as collaboration between WHO and Department of Community Health, University of Ghana Medical School. A nationally representative sample of 5571 older adults (≥50 years) and a small sample of persons 18–49 years were interviewed. Data was obtained on uptake of cataract surgery in older adults and analyzed using descriptive measures and chi square for associations in categorical outcome measures. RESULTS: Overall surgical uptake was 48.9% among older adults and was slightly higher among older men (49.1%) than women (48%). Cataract surgical uptake was relatively higher in the 60–69 years group (55%), urban residents (52.6%) and those living without partners (50%). Educational and income levels of older persons did not affect cataract surgical uptake. Regional differences in cataract surgical uptake existed; was less than 60% in all ten regions (except one), and the two regions with most self-reported cataracts (Ashanti and Greater Accra) had less than 50% uptake. CONCLUSIONS: Intensive public education, engagement of community groups and increased access to cataract surgery at health facilities and outreach services need consideration at national/sub-national levels. Further investigations to garner equity in national eye care efforts are recommended.